Hukum dan Sosial dalam Hubungan Kemitraan Jasa Angkutan Aplikasi Daring - Yuhastina (LPPM Universitas Terbuka, 2023)
This study analyzes the partnership relationship between Online Application Transportation Service companies (JAAD) and drivers in legal sociology. The transportation service company is an association of several capital owners to create an application-based transportation business in the network (online). Its presence is not necessarily followed by the availability of adequate statutory instruments. As a result, quite complicated legal issues arise related to the weak legal protection of partners from the JAAD company. Weak legal protection can lead to social and legal precariatization of partners by citizenship. This is important considering that the partners of the In-network Application Transportation Services (JAAD) company, of whom there are millions, are citizens of the Republic of Indonesia who are under the auspices of the constitution. This study used a qualitative research method with a normative and comparative approach to a number of laws, government regulations, and ministerial regulations. In addition, the legal sociology approach was used to obtain qualitative data related to social and legal aspects of vulnerability and resistance. The results of the study showed that JAAD requires many people to earn income but the legal protection for JAAD’s corporate partners is weak, so they tend to be disadvantaged, exploited so that partners experience social, political and legal precariatization.